Mechanisms of the Legal Protection of Human Rights in Global Regulation - M A Hamad, Ahmed; Jannial, Jacklyn; Indriyani, Rachma (Serikat Pengajar Hak Asasi Manusia Indonesia, 2022)
This article addressed the issue of violations and infringements by presenting a legal study of the most important human rights protection mechanisms at the level of global regulation. The scientific necessity necessitated the study of the role of international bodies in the field of human rights, through the international mechanisms for monitoring human rights and the oversight and protection system in them. The article examined that international law has provided humanity with a number of mechanisms whose application leads to the creation of a virtuous society in which all human beings enjoy peace and security and enjoy all rights on an equal footing. International law has adopted a set of mechanisms that include a set of provisions that criminalize every act that would harm a person, whether this act occurred on his body, honor, or religion. International law has also created a number of consensual mechanisms that undertake the task of supervising and monitoring the extent to which individuals and states respect and apply those provisions. To achieve the objectives of the article, doctrinal legal research methodology using a qualitative approach was adopted. This article referred to a number of international treaties, charters, and declarations related to human rights or international law, in addition to many studies that dealt with human rights in international law. The article recommended that every country in the world shall stipulate that its constitution or basic law include explicit provisions that guarantee the protection of human rights and provide the necessary guarantees for their implementation.